Diketopyrrolopyrrole-based polymer:fullerene nanoparticle films with thermally stable morphology for organic photovoltaic applications. (2nd February 2017) - Holmes, Natalie P.; Vaughan, Ben; Williams, Evan L.; Kroon, Renee; Anderrson, Mats R.; Kilcoyne, A.L.David; Sonar, Prashant; Zhou, Xiaojing; Dastoor, Paul C.; Belcher, Warwick J.
Abstract: Abstract : Polymer:fullerene nanoparticles (NPs) offer two key advantages over bulk heterojunction (BHJ) films for organic photovoltaics (OPVs), water-processability and potentially superior morphological control. Once an optimal active layer morphology is reached, maintaining this morphology at OPV operating temperatures is key to the lifetime of a device. Here we study the morphology of the PDPP-TNT (poly3, 6-dithiophene-2-yl-2, 5-di(2-octyldodecyl)-pyrrolo[3, 4-c]pyrrole-1, 4-dione- alt -naphthalene):PC71 BM ([6, 6]-phenyl C71 butyric acid methyl ester) NP system and then compare the thermal stability of NP and BHJ films to the common poly(3-hexylthiophene) (P3HT): phenyl C61 butyric acid methyl ester (PC61 BM) system. We find that material T g plays a key role in the superior thermal stability of the PDPP-TNT:PC71 BM system; whereas for the P3HT:PC61 BM system, domain structure is critical.